Consequences of Drought Stress Encountered During Seedling Stage on Physiology and Yield of Cultivated Cotton - Rehman, Tanzeela; Tabassum, Bushra; Yousaf, Samina; Sarwar, Ghulam; Qaisar, Uzma (Frontiers in Plant Science, 2022)
Survival of the living organisms depends on the availability of water resources required for agriculture. In the current scenario of limited water resources, it is our priority to exploit the maximum yield potential of crops with minimum supply of available water. In this study, we evaluated seven cultivated varieties of G. hirsutum (FH-114, FH-152, FH-326, FH-492, FH-942, VH-327 and FH-NOOR) for their tolerance, yield potential and fiber quality under water shortages. We also studied the effect of drought stress on osmoregulation, chlorophyll content, antioxidant (Peroxidase and catalase) activity, lipid peroxidation and secondary metabolite accumulation in the varieties under study. It was revealed that three varieties (FH-114, FH-152 and VH-327) exhibit lower stress susceptibility index and more tolerance to the drought stress. All the varieties demonstrated enhancement of proline and malondialdehyde content but no significant change in chlorophyll content was observed in limited water supply. Antioxidant activity offered by catalase and phenolic content was enhanced in FH-492 while peroxidase activity increased in FH-114 and FH-326. Phenolic content was highest in FH-942 and decreased significantly in the remaining varieties. Ginning out turn of the cotton varieties demonstrated that it is increased in VH-327 (19.8%) and FH-326 (3.7%), not affected in FH-114 and FH-492 and negatively affected in FH-152, FH-942 and FH-NOOR. All the varieties of cotton showed increase in micronaire thickness when exposed to drought stress as early as seedling stage. This is an important study highlighting the evaluation and screening of cotton varieties for their response to drought stress in terms of yield and fiber quality when exposed to water shortages during plant development and can help in devising the irrigation plan.